Ultrasound assessment of lacrimal glands: a cross-sectional study in healthy subjects and a preliminary study in primary Sjögren's syndrome patients - De Lucia, Orazio; Zandonella Callegher, Sara; De Souza, Mirian Veronica; Battafarano, Norma; Del Papa, Nicoletta; Gerosa, Maria; Giovannini, Ivan; Tullio, Annarita; Valent, Francesca; Zabotti, Alen; Caporali, Roberto; De Vita, Salvatore (Clinical and experimental rheumatology, 2020)
This study aimed to: i) perform an ultrasonographic (US) evaluation of the lacrimal glands (LGs) in healthy subjects in order to define the sonographic elementary lesions which could be identified in the LGs and describe their frequencies in healthy subjects; ii) test the intra and inter-rater agreement between four rheumatologists; iii) preliminary assess whether the elementary lesions of the LGs let us differentiate healthy subjects from primary Sjögren's syndrome (pSS) patients.OBJECTIVESThis study aimed to: i) perform an ultrasonographic (US) evaluation of the lacrimal glands (LGs) in healthy subjects in order to define the sonographic elementary lesions which could be identified in the LGs and describe their frequencies in healthy subjects; ii) test the intra and inter-rater agreement between four rheumatologists; iii) preliminary assess whether the elementary lesions of the LGs let us differentiate healthy subjects from primary Sjögren's syndrome (pSS) patients.A consensus meeting was held to define the sonographic lesions to be evaluated. Healthy subjects and pSS patients underwent lacrimal glands ultrasound (LGUS) examinations in two Italian Rheumatology Clinics. A web-based reliability exercise was performed on healthy subjects' images by four rheumatologists. Afterward, images of pSS patients were evaluated for the presence of the sonographic lesions previously defined and compared to the US findings in healthy subjects.METHODSA consensus meeting was held to define the sonographic lesions to be evaluated. Healthy subjects and pSS patients underwent lacrimal glands ultrasound (LGUS) examinations in two Italian Rheumatology Clinics. A web-based reliability exercise was performed on healthy subjects' images by four rheumatologists. Afterward, images of pSS patients were evaluated for the presence of the sonographic lesions previously defined and compared to the US findings in healthy subjects.Fifty-seven healthy subjects and 17 pSS patients were evaluated. The intra and inter-rater reliability score was good-excellent for almost all the agreed US features assessed (glandular parenchyma visibility, size, homogeneity, hypoechoic areas, hyperechoic spots, fibrous gland appearance, fatty deposition). Among the LGUS elementary lesions in pSS patients compared with healthy subjects, we detected a significantly difference in glandular inhomogeneity [13/33 (39.4%) vs. 9/63 (14.3%), p=0.01], and in fibrous gland appearance [3/33 (9.1%) vs. 0/63 (0%), p=0.04].RESULTSFifty-seven healthy subjects and 17 pSS patients were evaluated. The intra and inter-rater reliability score was good-excellent for almost all the agreed US features assessed (glandular parenchyma visibility, size, homogeneity, hypoechoic areas, hyperechoic spots, fibrous gland appearance, fatty deposition). Among the LGUS elementary lesions in pSS patients compared with healthy subjects, we detected a significantly difference in glandular inhomogeneity [13/33 (39.4%) vs. 9/63 (14.3%), p=0.01], and in fibrous gland appearance [3/33 (9.1%) vs. 0/63 (0%), p=0.04].In this preliminary study, LGUS proved to have a good-excellent intra and inter-rater reliability. The glandular parenchyma inhomogeneity and the fibrous gland appearance could help differentiate pSS patients from healthy subjects.CONCLUSIONSIn this preliminary study, LGUS proved to have a good-excellent intra and inter-rater reliability. The glandular parenchyma inhomogeneity and the fibrous gland appearance could help differentiate pSS patients from healthy subjects.